MEMPELAJARI KINERJA BAJAK SINGKAL TIPE SLATED BERBAHAN BAJA STAINLESS PADA PERUBAHAN KECEPATAN KERJA DAN KEDALAMAN OLAH - Kemas M Ismail; Hersyamsi Hersyamsi; Endo Argo Kuncoro (Universitas Sriwijaya, 2012)
The objective of this research was to study the performance of stainless steel type slated mouldboard plow at several forward speeds and tillage depths. The research was conducted at the Experimental Farm of Agricultural Faculty and Chemical Laboratory, Biology and Fertility of Land, Soil Science, Sriwijaya University, Indralaya, from October to December 2011. This research was performed using Randomized Factorial Block Design that consisted of three levels of depth of the plough (10 cm, 15 cm, and 20 cm), and three levels of forward speed (2 km/hr, 3 km/hr dan 4 km/hr), and each treatment was repeated three times. The observed parameters were efficiency of tillage, energy’s need of tillage, and draft of tillage. The result showed that, the depth of tillage and the forward speed of tillage had very significant effect on the performance of tillage. The best treatment was the depth of tillage 10 cm and forward speed of tillage 2 km/hr, with efficiency of tillage 90.52 %, energy’s need of tillage 748.98 MJ/ha and draft of tillage 6.87 kg. Keywords: mouldboard plow, type slated, stainless steel.